Kisaran Inang dan Keragaman Gejala Infeksi Turnip Mosaic Virus - Eliza Suryati Rusli; Sri Hendrastuti Hidayat; Gede Suastika; Utomo Kartosuwondo (Jurnal Perlindungan Tanaman Indonesia, 2007)
The incidence of mosaic disease on vegetable crops in Indonesia has been reported recently. The disease is caused by TuMV which is considered as a new and important virus on caisin and turnip in Indonesia. Field survey has been conducted to determine disease incidence in vegetable growing areas. Symptom variability and host range of TuMV was further studied through mechanical inoculation to cruciferae and solanaceae plants. Observation during field survey has proved that TuMV has infected caisin and turnip in Java and Bali. The highest intensity of mosaic disease i.e. 63,3% occurs in Tumpangan-Malang, followed by Denpasar Selatan and Bandungan-Semarang with the intensity of 30,5% and 19,0% respectively. TuMV infection causes different types of symptoms, such as: wrinkled leaf, blistered leaf, vein banding, vein clearing, leaf distortion and proliferation. The host range of TuMV involves those plants belong to cruciferae (cabbage, broccoli, caisin, turnip, cauliflower, chinese cabbage, pak coy); solanaceae (N. tabacum, N. benthamiana, N. glutinosa); and chenopodiaceae (C. amaranticolor). Furthermore, N. glutinosa can be used as differential host for TuMV isolates.